2018
DOI: 10.1093/aob/mcy140
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal variation in the pollination systems of a supergeneralist plant: isAngelica sylvestris(Apiaceae) locally adapted to its most effective pollinators?

Abstract: Angelica sylvestris is morphologically well adapted to ecological generalization, and there is little evidence that the surveyed populations represent distinct pollination ecotypes. Most likely, the observed variation in floral characters can be interpreted as 'adaptive wandering'. Specialization in this family seems possible only under very special circumstances, for example when the pollinator community comprises insect visitor groups that clearly differ in their pollination capacity (e.g. due to differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 98 publications
(140 reference statements)
3
38
0
1
Order By: Relevance
“…Accordingly, the spatiotemporal variation of the most effective pollinator is the factor most frequently advocated to explain the emergence and maintenance of generalist pollination systems. Several studies have explored temporal variation in composition and frequency of floral visitors (Fenster & Dudash, 2001;Ivey, Martinez & Wyatt, 2003;Zych et al, 2018). Other studies have quantified the effectiveness (i.e., the product of efficacy times visitation rate, after Herrera (1987) and Freitas (2013)) of different pollinator species or functional groups (Amorim, Galetto & Sazima, 2013;Salas-Arcos, Lara & Ornelas, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the spatiotemporal variation of the most effective pollinator is the factor most frequently advocated to explain the emergence and maintenance of generalist pollination systems. Several studies have explored temporal variation in composition and frequency of floral visitors (Fenster & Dudash, 2001;Ivey, Martinez & Wyatt, 2003;Zych et al, 2018). Other studies have quantified the effectiveness (i.e., the product of efficacy times visitation rate, after Herrera (1987) and Freitas (2013)) of different pollinator species or functional groups (Amorim, Galetto & Sazima, 2013;Salas-Arcos, Lara & Ornelas, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Since nectar production is under pollinator-mediated selection, parameters such as composition, volume, and sugar concentration may be highly variable between plant species [ 1 , 7 , 8 ]. Earlier studies of nectar diversity have postulated that some nectar features, such as sugar and AA profiles, are species-invariant [ 7 , 9 , 10 , 11 ], and some new analyses support a rather conservative proportion of nectar components, that is sugars, between populations of the same species (e.g., [ 12 ]). However, this notion seems to be the result of technical difficulties associated with early analytical methods [ 3 , 13 ] because many recent studies have reported variation in nectar traits between populations, within populations, within one inflorescence, or even among sexual phases of the same flower [ 8 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies of nectar diversity have postulated that some nectar features, such as sugar and AA profiles, are species-invariant [ 7 , 9 , 10 , 11 ], and some new analyses support a rather conservative proportion of nectar components, that is sugars, between populations of the same species (e.g., [ 12 ]). However, this notion seems to be the result of technical difficulties associated with early analytical methods [ 3 , 13 ] because many recent studies have reported variation in nectar traits between populations, within populations, within one inflorescence, or even among sexual phases of the same flower [ 8 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Such variations are mainly a consequence of environmental factors, such as soil properties, air temperature, and sun exposure [ 1 , 2 , 8 , 13 , 21 ], and, according to the latest study, microorganisms inhabiting nectar [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Manuscript to be reviewed variation of the most effective pollinator is the factor most frequently advocated to explain the emergence and maintenance of generalist pollination systems. Several studies have explored temporal variation in composition and frequency of floral visitors (Fenster & Dudash, 2001;Ivey, Martinez & Wyatt, 2003;Zych et al, 2018). Other studies have quantified the effectiveness (i.e., the product of efficacy times visitation rate, after Herrera, 1987;Freitas 2013) of different pollinator species or functional groups (e.g., Amorim, Galetto & Sazima, 2013;Salas-Arcos, Lara & Ornelas, 2017).…”
Section: Introductionmentioning
confidence: 99%